Associations among Hypertension, Depression and Obesity in a sample of the U.S. adults: IJPDS (2017) Issue 1, Vol 1:011, Proceedings of the IPDLN Conference (August 2016) - Kim, Hyunmin; Setias, Jade (International Journal of Population Data Science, 2017)
ABSTRACT Objective Although there have been studies showing the determinants of obesity, there have been relatively little attention paid to other factors such as mental health disorders like depression and chronic illnesses like hypertension. In addition, there exists a controversy over the association between hypertension and depression. Thus, we have investigated the associations among hypertension, depression, and obesity by adjusting age, gender, race, and socioeconomic status. The data was from the 2011 National Health and Nutrition Examination Surveys (NHANES). Method This survey is conducted every year and in particular the data involves approximately 5,000 individuals of all ages in the United States, who completed the health examination component of the survey. We have utilized a logistic regression analysis to examine how hypertension, depression and obesity are associated one another. We have also used a proportional odds model to test how hypertension and depression may affect obesity. Result The main findings from the results of study are the following: first, being obese and feeling down, depressed or hopeless were associated with an increased likelihood of having hypertension and second, hypertension and depression may positively affect obesity. The findings suggest that as the determinants of obesity, depression and hypertension should be timely diagnosed and treated properly for considering the associations one another. By doing so, it can provide with the overall cost-savings and more importantly, people’s health.